(untitled) (Medical Forum Monthly, 2024)
Objective: Pulpitis is one of the most prevalent dental conditions, and it’s most common treatment is root canal procedure, which is has limitations. Stem cell transplantation is the promising alternative treatment. Among the various sources of stem cells available, dental pulp stem cells and umbilical cord stem cells have distinct advantages over other sources. Study Design: In-vitro experimental study Place and Duration of Study: This study was conducted at the at MDRL- Ziauddin University, Karachi from April 2023 to April 2024. Methods: Dental pulp stem cells were isolated from dental pulp collected from healthy, extracted teeth. Umbilical cord stem cells were isolated from umbilical cord collected following a c-section. The cells were cultured and then population doubling time, and cell viability was assessed. Morphological analysis was also done, followed by gene expression analysis. Results: and conclusion: DPSCS showed a shorter population doubling time, and higher growth rate compared to UCMSCS, while expressing characteristic mesenchymal stem cell markers, making them an ideal stem cell source. Conclusion: DPSCS are a promising alternative cell source to UCMSCS for stem cell-based therapy. They have similar morphological features compared to UCMSCS and stem cell markers but have with higher proliferation capacity, significantly lower population doubling time, and high cell viability.